Interface characterization at nanometer scale using very high frequency ultrasounds. Issue 4 (3rd April 2019) - Reda, Hilal; Carlier, Julien; Toubal, Malika; Campistron, Pierre; Tilmant, Pascal; Nongaillard, Bertrand
ABSTRACT: The main objective of this work is to study the solid-solid interfaces using a very high frequency (3GHz) ultrasonic method in order to deduce in a non-destructive way and quantitatively the quality contact at the interface, fundamental parameter in tribology. The very high frequencies allow prospecting the state of contact at the nanometer scale. The determination of the contact surface between two polished materials (Silicon-Silica) was carried out. From the measured echoes diagram, the reflection coefficient and the elasticity of the interface were extracted and compared to the ones determined by a numerical approach presented by Greenwood and Williamson